PENGARUH SELF EFFICACY DAN LOCUS OF CONTROL DALAM MENINGKATKAN KINERJA KARYAWAN DI CASSANO CAFÉ MEDAN - Irvan Rolyesh Situmorang (Niagawan, 2023)
Human resources are one of the most important assets in a company or business, so entrepreneurs must pay special attention to these human resources in order to be able to improve the performance of human resources themselves. The purpose ofthis research is to determine the effect of  Self Efficacy and Locus of Control on Employee Performance at Cassano Café. The population and sample in this study were 30 respondents with a saturated sample. Data collection techniques using observations, questionnaires, and interviews. Data analysis techniques use multiple linear analysis. The results of multiple linear regression analysis are  Y = 11.137 + 0.795X 1 +  1.055X2 + e. The results of partial test research (t) show that Self Efficacy has a positive and significant effect on Employee Performance, Locus of Control also has a positive and significant effect on  Employee Performance.  The results of simultaneous test research (F) show that Self Efficacy  and Locus of Control have a positive and significant effect on Employee Performance.  The result of the coefficient of determination  of 69.8% for Employee Performance, while the remaining 32.5%, was influenced by other factors outside of this study.